Analisis Komparatif Algoritma Paparan Media Sosial dan Pola Kebiasaan Sarapan terhadap Status Gizi Remaja - Shinta Widya Murti; Muwakhidah Muwakhidah; Firmansyah Firmansyah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
This study aims to examine the relationship between the intensity of social media use and breakfast habits on the nutritional status of adolescents at SMP Negeri 6 Surakarta. The methodology employed was a cross-sectional design with a quantitative orientation and included 92 participants recruited using non-probability sampling techniques. Data collection regarding social media use was conducted using a validated questionnaire (Cronbach’s Alpha = 0.914), while breakfast habits were assessed using a 24-hour recall method over a one-week period, and nutritional status was evaluated using the Age-Adjusted Body Mass Index (BMI/A). Data analysis was conducted using the Chi-Square test. The study findings revealed that the majority of participants (82.6%) fell into the category of optimal social media use, 76.1% had breakfast habits that met their energy needs, and 53.3% had a normal nutritional status. However, 32.6% of participants showed signs of overnutrition and 6.5% were obese. The statistical test results indicated no significant association between social media use and nutritional status (p=0.817), nor was there an association between breakfast habits—as assessed by energy (p=0.421), protein (p=0.628), fat (p=0.672), and carbohydrate (p=0.496) intake—and nutritional status. It can be concluded that adolescents’ nutritional status is not solely influenced by social media use or breakfast habits, but rather results from the accumulation of various factors such as the overall quality of daily dietary patterns, physical activity levels, and family socioeconomic conditions.